1999
DOI: 10.1089/10430349950016438
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of Antiangiogenic Adenovirus AdmATF Induces Liver Resistance to Metastasis and Prolongs Survival of Mice

Abstract: Systemic administration of Ad5-based recombinant adenovirus leads to preferential transduction of the liver. Using this property, we have assessed the potential of venous viral injection to deliver a recombinant antiangiogenic adenovirus to treat cancer dissemination and improve survival. The results demonstrate that venous injection of adenovirus AdmATF, which encodes a secretable mouse ATF (amino-terminal fragment of urokinase) known to inhibit angiogenesis, suppressed angiogenesis induced by colon cancer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 24 publications
2
31
3
Order By: Relevance
“…A recombinant adenovirus encoding the noncatalytic ATF of mouse uPA prevents lung carcinoma metastasis 10 and protects mice in a liver metastasis model of human colon carcinoma. 11 A marked reduction in tumoral neovascularization was observed in these experiments.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…A recombinant adenovirus encoding the noncatalytic ATF of mouse uPA prevents lung carcinoma metastasis 10 and protects mice in a liver metastasis model of human colon carcinoma. 11 A marked reduction in tumoral neovascularization was observed in these experiments.…”
Section: Introductionsupporting
confidence: 56%
“…The angiostatic activities of ATF and endostatin have already been described in numerous tumor models. 10,11,13,15 This is the first time that AFT has been shown to have angiostatic activity in a model of retinal neovascularization. We showed that that local gene transfer and the expression of ATFHSA reduce retinal neovascularization by 78.1%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recombinant adenovirus encoding the non-catalytic ATF of mouse uPA has been previously shown to prevent lung carcinoma metastasis 15 and to protect mice in a liver metastasis model of human colon carcinoma. 16 In these experiments, a marked reduction in the tumoral neovascularization was observed. Because ATF binds to uPAR on cell surfaces, it disrupts the interaction of uPA to its receptor (uPAR) and inhibits uPA/uPAR-dependent angiogenesis process by preventing plasminogen conversion into plasmin, and subsequent activation of the proteolytic cascade required for extracellular matrix degradation and cell invasion.…”
Section: Introductionmentioning
confidence: 70%
“…[20][21][22][23][24][25][26] The above-mentioned studies provide important information on the relative potency of a number of antiangiogenic gene products previously shown to possess antitumor activity. 10,11,13,14,[27][28][29][30][31] However, there is a dearth of information on the antitumor activity of Can. Our objective was to determine the sensitivity of an intraocular HSA-fused angiostatic factors block metastasis E Frau et al been suboptimal.…”
Section: Discussionmentioning
confidence: 99%